Dual-Task Performance in Multiple Sclerosis' Patients: Cerebellum Matters?. (17th October 2020) - Argento, Ornella; Spanò, Barbara; Pisani, Valerio; Incerti, Chiara C; Bozzali, Marco; Foti, Calogero; Caltagirone, Carlo; Nocentini, Ugo
Abstract: Objective: Gait, cognitive impairments, and their mutual influence in dual tasking (cognitive–motor dual tasking, CM-DT) are important to address therapeutic approaches in patients with multiple sclerosis (PMS). CM-DT correlates have been widely investigated with variable and dissimilar results, due to differences in methods. However, although the cerebellum has recently shown to be involved in both motor and cognitive functions, few studies have explored its role in the integration of the concurrent execution of gait and cognition. This case–control study aims to explore the effects of adding a cognitive task to walking in PMS and to investigate the role of the cerebellum in the interfering process. Methods: In total, 20 patients and 18 healthy controls (HC) underwent clinical assessments, dual task (DT), and 3 T magnetic resonance imaging (MRI). DT was composed by three 2-min trials requiring fast walking. In 2 of them 2 different cognitive tasks were added. Results: Both groups evidenced the presence of cognitive–motor interference (CMI) for both cognitive conditions with a greater effect of word list generation task in PMS. Analysis of variance between HC and patients with high or low performances showed a significantly increased volume in Vermis lobules VIIIa and IX of high performers compared with HC. Conclusion: Our results show that CMI is also present in healthy individuals but is significantly more disabling in PMS. Furthermore, MRI data point to the existence of an initial mechanism of cerebellar reorganization in PMS with lower interference. Subsequently, the failure of this mechanism due to the progression of disability leads to a more evident expression of symptoms.